Union of the Comoros : Poverty Reduction Strategy Paper: Progress Report: Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2013)
This review is on Comoros' first full Poverty Reduction Strategy (CPRS). The macroeconomic developments outlined in the progress report are broadly in line with the assessment. Key policy challenges remain for the future. Progress in strengthening budget management has mixed during the report period. Despite reform momentum, which has picked up recently, the progress report correctly characterizes developments in the energy sector as falling short of expectations during 2011. Deficient transport and telecommunication infrastructures are important constraints to the development of the Comorian economy.